Biological Studies on Dipha aphidivora Meyrick (Pyralidae: Lepidoptera): A Potential Predator of Coconut Mealybugs in the Philippines - J.C. Orense; M.L.R. Imperial (CORD, 2010)
Dipha (Conobathra) aphidivora Meyrick (Pyralidae: Lepidoptera) is recorded for the first time as a predator of coconut mealybug, Sangicoccus sp. (Eriococcidae: Homoptera)) in the Philippines. Some aspects of its biology and ecology were studied to determine its suitability as a biological control agent against Sangicoccus sp. The life history of D. aphidivora was investigated following the establishment of a rearing procedure. The incubation period of the egg was 4.64±0.70 days. The four larval instars larva were completed in 5.52±0.92, 3.40±0.91, 2.83±0.72 and 3.40±1.04 days, respectively. Adults emerged from pupae after 7.68± 0.99 days. Adult longevity was 6.83 ± 2.30 days. The life cycle of D. aphidivora lasted for 32.42±3.63 days. Voracity tests showed that the four larval instars of the predator consumed an average of 150 mealybugs.